Prevalence of non-Alcoholic Fatty Liver Disease and Associated Factors in Patients with Moderate or Severe Hemophilia: A Multicenter-Based Study. (September 2022) - Shen, Ming-Ching; Chiou, Shyh-Shin; Chou, Sheng-Chieh; Weng, Te-Fu; Lin, Ching-Yeh; Wang, Jiaan-Der; Lee, Shou-Wu; Peng, Ching-Tien
Introduction: Liver health is essential for persons with hemophilia (PWH) in order to maintain access to new therapies, such as gene therapy. Non-alcoholic fatty liver disease (NAFLD) is seldom reported in the hemophilia population. The study aimed to investigate the prevalence of NAFLD and associated factors in PWH. Methods: Data of this cross-sectional study were obtained from a multicenter collaborative registry database. Results: A total of 163 moderate or severe PWH with a complete data of liver examination were analyzed. There were 77 (47.2%) PWH diagnosed with NAFLD. The multivariate analysis showed that overweight/obesity was associated with NAFLD (OR, 4.31, P  < .001). In comparison with hemophilia B patients, hemophilia A patients showed a weaker correlation with NAFLD, (OR, 0.30, P  = .009). A total of 17 (25.8%) PWH with NAFLD had an elevated level of alanine transaminase (ALT). Both overweight/obesity and presence of inhibitor to clotting factor were independently associated with elevated ALT in PWH with NAFLD. Conclusions: The study indicated that a high prevalence of NAFLD existed in the hemophilia population. Overweight/obesity was an independent factor for NAFLD and elevated ALT.